Source-independent quantum random number generators with integrated silicon photonics - Yongqiang Du; Xin Hua; Zhengeng Zhao; Xiaoran Sun; Zhenrong Zhang; Xi Xiao; Kejin Wei (Communications Physics)
Abstract Random numbers play a crucial role in numerous scientific applications. Source-independent quantum random number generators (SI-QRNGs) can offer true randomness by leveraging the fundamental principles of quantum mechanics, eliminating the need for a trusted source. Silicon photonics demonstrates significant promise for QRNG due to its benefits in miniaturization, cost-effective device manufacturing, and compatibility with CMOS microelectronics. This study experimentally demonstrates a silicon-based discrete variable SI-QRNG. Our SI-QRNG system achieves a low error rate of only 0.21%, thanks to the inherent stability of the silicon-based decoder chip and its excellent polarization extinction ratio. Additionally, by using a laser with a higher repetition rate and a robust simulation model, we achieve the highest quantum random number generation rate of 9.49 Mbits per second. Our research paves the way for integrated SI-QRNGs, providing a cost-effective and robust secure QRNG module for next-generation communications.